Law Enforcement Against Perpetrators of Diploma Forgery Crimes in the Jurisdiction of Samarinda Police Resort - Ramadhanty, Nia Syafira; Lisi, Ivan Zairani; Syarifuddin , La (IHSA Institute, 2024)
Abstract: This study examines the enforcement of legal actions against perpetrators of diploma forgery crimes within the jurisdiction of the Samarinda Police Resort. Focusing on both procedural and substantive legal approaches, the research explores the implications of legal enforcement efforts in addressing document falsification as a criminal offense. Using normative juridical methods, the research highlights challenges faced by law enforcement in proving criminal intent and ensuring adequate penalties for deterrence. This research contributes to the discourse on improving criminal law systems in combating intellectual fraud while safeguarding the credibility of academic credentials. Keywords: Diploma Forgery; Legal Enforcement; Samarinda Police Resort; Criminal Law; and Law Deterrence.